Isolation of proteinase K-sensitive prions using pronase E and phosphotungstic acid. - Laura D'Castro; Adam Wenborn; Nathalie Gros; Susan Joiner; Sabrina Cronier; John Collinge; Jonathan D F Wadsworth (PLoS ONE)
Disease-related prion protein, PrP(Sc), is classically distinguished from its normal cellular precursor, PrP(C), by its detergent insolubility and partial resistance to proteolysis. Molecular diagnosis of prion disease typically relies upon detection of protease-resistant fragments of PrP(Sc) using proteinase K, however it is now apparent that the majority of disease-related PrP and indeed prion infectivity may be destroyed by this treatment. Here we report that digestion of RML prion-infected mouse brain with pronase E, followed by precipitation with sodium phosphotungstic acid, eliminates the large majority of brain proteins, including PrP(C), while preserving >70% of infectious prion titre. This procedure now allows characterization of proteinase K-sensitive prions and investigation of their clinical relevance in human and animal prion disease without being confounded by contaminating PrP(C).